Radiocarbon ages of sediment core IDLE-MAT10-2B from Lake Matano in Sulawesi, Indonesia - Meredith Parish; James M Russell; Bronwen Konecky; Xiaojing Du; Chengfei He; Satria Bijaksana; Hendrik Vogel (PANGAEA, 2024)
We produced an age model based on radiocarbon dates measured in the 8-m composite Lake Matano sediment core that spans the last deglaciation. There are 11 radiocarbon ages in the 8 m core.